Geopolitical Challenges in Public Governance - Aslam, Mohd Mizan Mohammad; Mahadi, Syed Razak Syed; Mizan, Muhd Nabhan (International Journal of Strategic Studies, 2024)
Geopolitics is the study of how Earth's geography both physical and human, affects politics and international relations. The Ancient Greek terms γῆ (gê), which means "earth, land," and πoλιτική (politikḗ), which means "politics," are the source of the term "geopolitics.". It is an academic discipline that studies how a nation's size, location, climate, terrain, population, and natural resources affect its politics, particularly its foreign policy. Geopolitics has a significant bearing on public governance. A framework for comprehending the power relationships that shape our world is provided by geopolitics. It aids in the analysis of how geopolitical forces affect human rights, cultural heritage, and the development of public opinion around the world. Insights into societal divides, migration trends, and the emergence of nationalism are also provided by it. Other than that, geopolitical factors can impact governance strategies in the context of governance. For instance, decision-making procedures within public governance, strategic planning, and policy-making may be impacted by the geopolitical backdrop of a given area. It may also have an impact on how various countries relate to one another, which could have an impact on international accords and policies. Additionally, geopolitics can be understood as a process that makes it easy to comprehend conflicts and tensions at several levels, including local, regional, national, and worldwide. It can also disclose power struggles between actors. This knowledge can help public governance manage these tensions and conflicts in an efficient manner. In essence, geopolitics is a major factor in determining the tactics and laws used in public government. It offers a prism through which we can view the intricate relationships that are necessary for efficient public governance, including those involving geography, power, politics, and international relations. Thus, a better understanding of geopolitics can support more intelligent, astute, and successful public governance.